2017
DOI: 10.1136/svn-2016-000041
|View full text |Cite
|
Sign up to set email alerts
|

Review of acute ischaemic stroke in Pakistan: progress in management and future perspectives

Abstract: Ischaemic stroke is a major cause of neurological morbidity and mortality. The objective of this review article is to summarise facts pertaining to acute ischaemic stroke and its various aspects in a developing country like Pakistan, where resources are limited and the healthcare system is underdeveloped. No large-scale epidemiological studies are available to determine the true incidence of stroke in Pakistan. We reviewed the available literature on stroke from Pakistan and through this article we primarily a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 25 publications
1
32
0
Order By: Relevance
“…Tissue plasminogen activator, as a registered medical product by the Ministry of Health Pakistan, has extremely limited availability. Efforts are being made by the neurologist community in Pakistan to address this lack of availability [11]. However, before thrombolysis can be the norm for treatment for acute stroke, public understanding of stroke and its risk factors and warning signs has to improve.…”
Section: Discussionmentioning
confidence: 99%
“…Tissue plasminogen activator, as a registered medical product by the Ministry of Health Pakistan, has extremely limited availability. Efforts are being made by the neurologist community in Pakistan to address this lack of availability [11]. However, before thrombolysis can be the norm for treatment for acute stroke, public understanding of stroke and its risk factors and warning signs has to improve.…”
Section: Discussionmentioning
confidence: 99%
“…Stroke Risk in Atrial Fibrillation Working Group found that for patients with AFib and hypertension, the risk of stroke increases 1.6 to 2.5 times compare with patients without AFib. 29 They also found that a history of hypertension and systolic blood pressure >160 mm Hg was independently and separately associated with an increased risk of www.theprofesional.com ISCHEMIC STROKE 88 5 stroke in patients with AFib. 29 Hyperthyroidism in our study was present among 4.5% patients with atrial fibrillation.…”
Section: This Study Was Conducted In Medical Andmentioning
confidence: 99%
“…These risk factors are well known and can be modifiable and non-modifiable. [3][4][5] Older age and 2 atrial fibrillation were independently associated with greater risk for developing pneumonia in California Acute Stroke Prototype Registry. Other factors include atrial fibrillation and dyslipidemia.…”
Section: Introductionmentioning
confidence: 98%